Zur Massenvermehrung und Überwachung von Frostspannerarten in der Forstwirtschaft der DDR in den Jahren 1958-1960. - Fankhänel, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1961)
An outbreak of the Small Winter Moth(Operophthera brumata L.), which was accompanied by severe damages caused by both the Mottled Umber Moth (Erannis defoliaria Cl.) and the Scarce Umber (Erannis aurantiaria Esp.) culminated in 1956/1957 in the district of the "Börde" and the central German inland climate. Until 1959/1960 there was observed a shifting of the defoliation centres from South-West to North-East, quite similar to this phenomenon during an outbreak of Tortrix viridana L. In the course of the outbreak a distinct amount of population density during a period of 3-4 years could be locally observed. In this paper are given results on flight time, sex ratio, and fecundity. Apart from abiotic factors a special significance is due to the 15 reared species of parasites and hyperparasites (above all: Apúnteles solitarius Ratz, and Phobocampe crassiuscula Grav. and the tachinid flies Blondelia nigripes Fall. and Phryxe longicauda Wwr.). A glue ring method (Leimringmethode), already described and tested over 3 years in practice, to ascertain critical numbers (number of moths: width round the trunk) on 10 representative control trunks within a stock of trees was found a useful indicator for an outbreak to be expected.